AN ANALYSIS OF TEACHERS’ STRATEGY IN TEACHING ENGLISH VOCABULARY DURING COVID-19 - Rahman, Arif (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
The main objective of teaching English is to explores and describes the strategies used by the teacher, problem faced by the teacher, and problem solved by the teacher in teaching vocabulary. A descriptive qualitative conducted to analyze the data of the study. The data were taken from interview, observation and document with participant are the English teacher of SMP IT IMISc Labuapi. Furthermore, this study focuses on the process of teaching vocabulary to the first-grade students in SMP IT IMISc Labuapi. Based on the class observation, interview, and document, this study shows that there are some strategies conducted by the teachers, i.e.: (1) memorization, (2) synonym/antonym, (3) translating, and (4) fill in the blank. The problems faced by the teacher are: (1) classroom management, (2) student’s motivation and (3) student’s laziness. The problems solved by the teacher are: (1) she called the students who make noisy and asked them some questions about the material or she ordered the student who was noisy to go out, (2) the teacher gave advice and motivation about the importance of English subject and the importance to improve the vocabulary. Besides, the teacher also implemented another strategy by giving score to the active students. The students also can consult the difficult materials with the teacher out of class, (3) the teacher gave new vocabulary that wrote in the whiteboard every meeting to improve their vocabulary. The strategies used by the teacher are good because the strategies can make the students more active. Besides that, the strategies used by the teacher can make the students interested in following the class.